Endoscopic Endonasal Transsphenoidal Surgery for Resection of Craniopharyngioma in Pediatric Population: A Comprehensive Review of the Literature - Fouda, Mohammed A. (Journal of Pediatric Neurology, 2023)
Craniopharyngioma is a rare epithelial brain tumor which arises from the embryological remnants of Rathke's pouch—a remnant of the primitive pharynx. The proximity of this tumor to the pituitary stalk, hypothalamus, third ventricle, optic chiasm, and optic nerves, as well as the major intracranial vessels bridging this area, makes safe surgical resection challenging. Given the recent advancement in endoscopic surgical techniques and the intraoperative assistance of neuronavigation and intraoperative magnetic resonance imaging, endoscopic endonasal transsphenoidal surgery (EETS) can be an alternative to the open transcranial approaches in the management of children with craniopharyngioma who fulfill the appropriate selection criteria. The comparison between the EETS and the open transcranial approach regarding the clinical and surgical outcomes could be subject to an inherent selection bias. In this article, we reviewed the body of the literature on the role of EETS in the management of pediatric craniopharyngioma and the proper selection criteria of children with craniopharyngioma, who might be suitable candidates for tumor resection via this minimally invasive endoscopic approach. We also looked at the preoperative assessment, surgical techniques, surgical and clinical outcomes, and the possible complications of endoscopic endonasal transsphenoidal surgery.
Keywords: pediatric; craniopharyngioma; endoscopic; transsphenoidal; CSF leak